E.M. Forster's Homoerotic Short Stories as Reorientation. - Hueso-Vasallo, Manuel (My University, 2020)
E.M. Foster’s impact on the literary representation of homosexual relationships and desire is widely acknowledged nowadays. This is due, mainly, to his 1914 novel Maurice, published posthumously in 1971. His lesser-known short stories that deal with homoerotic encounters and tensions, on the other hand, have traditionally been dismissed as the author’s manifestation of his personal fantasies, or even as sexual indulgences. These stories, however, provide a very significant insight into the way in which Forster creates a new and personal code for the representation of homosexuality that disrupt previous, more traditional Victorian ways of representing this sexual identity.
Keywords: Teoría queer; Homosexualidad en la literatura; Forster, E.M.- Crítica e interpretación; Sara Ahmed; E.M. Forster; Short stories